“Fada’at Alyamamah Al’Adhraa” of the poet Ali Al Fazani (Virgin Dove Spaces).: دراسة بنيوية (Journal of Human Sciences, 2020)
This research analyzes Divan of “Fada’at Alyamamah Al’Adhraa” of the poet Ali Al Fazani  (Virgin Dove Spaces) a compositional analysis. This Divan that described an experiment in which the poet had been engaged with a new Compositional and Textural poetic method to make the two pieces of this Divan “ Alsu’oud  Wa  Thuna’eyat Alme’araje” (The Rising & Duet of Ascent) a modern and contemporaneous pieces of poetry; However this Divan creates a dual dialogue being opened and discovered by breaking the code to figure out the hidden energies. Otherwise its composition consists of a dual antagonism of a great importance to clarify its essentiality which  enforces itself on reader to dive into the meaning.This duet is duet of rising to space and flying through skies facing ascent through space to land into earth in peace.